Integration of Merged Delayed‐Enhanced Magnetic Resonance Imaging and Multidetector Computed Tomography for the Guidance of Ventricular Tachycardia Ablation: A Pilot Study. (17th December 2012) - COCHET, HUBERT; KOMATSU, YUKI; SACHER, FREDERIC; JADIDI, AMIR SHERWAN; SCHERR, DANIEL; RIFFAUD, MATTHIEU; DERVAL, NICOLAS; SHAH, ASHOK; ROTEN, LAURENT; PASCALE, PATRIZIO; RELAN, JATIN; SERMESANT, MAXIME; et al.
<x xml:space="preserve">Abstract</x> MDCT/MRI Fusion for the Guidance of VT Ablation. Background: Delayed enhancement (DE) MRI can assess the fibrotic substrate of scar‐related VT. MDCT has the advantage of inframillimetric spatial resolution and better 3D reconstructions. We sought to evaluate the feasibility and usefulness of integrating merged MDCT/MRI data in 3D‐mapping systems for structure–function assessment and multimodal guidance of VT mapping and ablation. Methods: Nine patients, including 3 ischemic cardiomyopathy (ICM), 3 nonischemic cardiomyopathy (NICM), 2 myocarditis, and 1 redo procedure for idiopathic VT, underwent MRI and MDCT before VT ablation. Merged MRI/MDCT data were integrated in 3D‐mapping systems and registered to high‐density endocardial and epicardial maps. Low‐voltage areas (<1.5 mV) and local abnormal ventricular activities (LAVA) during sinus rhythm were correlated to DE at MRI, and wall‐thinning (WT) at MDCT. Results: Endocardium and epicardium were mapped with 391 ± 388 and 1098 ± 734 points per map, respectively. Registration of MDCT allowed visualization of coronary arteries during epicardial mapping/ablation. In the idiopathic patient, integration of MRI data identified previously ablated regions. In ICM patients, both DE at MRI and WT at MDCT matched areas of low voltage (overlap 94 ± 6% and 79 ± 5%, respectively). In NICM patients, wall‐thinning areas matched areas of low voltage (overlap 63 ± 21%). In patients with myocarditis, subepicardial DE matched areas of epicardial low voltage (overlap 92 ± 12%). A total number of 266 LAVA sites were found in 7/9 patients. All LAVA sites were associated to structural substrate at imaging (90% inside, 100% within 18 mm). Conclusion: The integration of merged MDCT and DEMRI data is feasible and allows combining substrate assessment with high‐spatial resolution to better define structure–function relationship in scar‐related VT. (J Cardiovasc Electrophysiol, Vol. 24, pp. 419‐426, April 2013)